A multi-type and decentralized data transaction scheme based on smart contracts and digital watermarks. (15th February 2021) - Xiang, Yuexin; Ren, Wei; Li, Tiantian; Zheng, Xianghan; Zhu, Tianqing; Choo, Kim-Kwang Raymond
Abstract: While data sharing cross management is increasingly popular, there are challenges in such a decentralized data sharing mode, especially in terms of transaction fairness and copyright protection. However, few schemes consider both fairness and copyright protection in the current literature. In this paper, we propose a flexible and Ethereum-based scheme to facilitate copyright protection in data sharing blockchain, by using watermark-based policies. This allows us to achieve properties such as preventing the re-selling of data (e.g., partial data, combined data, and leaked data). We also design five algorithms to automatically guarantee data sharing fairness and proactively protect data copyright, by using smart contracts. In other words, several new security features are introduced to existing transaction schemes, while still achieving feasible performance. The response times for each key step of smart contract in the proposed scheme is between 0.41 s and 0.91 s.